Relation of Airway Responsiveness to Methacholine to Parent and Child Reporting of Symptoms Suggecting Asthma. Issue 2 (3rd April 1996) - FitzGerald, JM; Fester, DE; Morris, MM; Schulzer, M; Hargreave, FE; Sears, MR
Abstract : BACKGROUND: The lack of a relationship between airway responsiveness and respiratory symptoms in epidemiological studies of children may, in part, reflect inaccuracies in symptom reporting or inadequate knowledge by the parent of the child's symptoms. OBJECTIVE: To relate airway responsiveness to methacholine in children with symptoms of respiratory illness in the child as reported by the parent and as reported by the child. POPULATION: Eight- to 10-year-old (n=290) randomly sampled schoolchildren. SETTING: Seven randomly selected schools in Ontario. METHODS: Parents completed a mailed questionnaire regarding the child's respiratory health. Children completed a similar interview-administered questionnaire at school and underwent methacholine challenge testing by the tidal breathing method. RESULTS: The cumulative prevalence of a history of physician-diagnosed asthma was 9.0%, and of any wheezing it was 25.5%. A further 9% of children reported wheezing not documented by their parent. Of 229 children consenting to methacholine challenge, 78 (34.1%) showed airway responsiveness in the range generally associated with asthma in adults (provocation concentration of methacholine causing a 20% fall [PC20 ] in forced expired volume in 1 s [FEV1 ] 8 mg/mL or less); half of these children had no history of respiratory symptoms reported by the parent. The sensitivity of airway hyperresponsiveness defined by a cut-point for PC20 8 mg/mL or less in relation to any history of recurrent wheezing reported by the parent was 48% and did not improve if only symptoms within the past year were considered (sensitivity 44%); the specificity of the test for parent-reported symptoms ever was 71%, and 68% in those with symptoms in the past year. None of these sensitivities or specificities was increased by using symptoms reported by the child or by combining parent and child reported symptoms. Receiver operating characteristic (ROC) curves for sensitivity and specificity of the methacholine test were constructed for parent and child reports of symptoms. For all symptom strata, the cut-point of PC20 producing optimal balance of sensitivity and specificity was between 4 and 8 mg/mL. A parental questionnaire positive for physician-diagnosed asthma was strongly related to methacholine response, producing an ROC curve with an area significantly different from 0.5 (P=0.006), as did all parent-reported wheezing (P=0.009). If the child reported asthma, there was an equally strong relationship, with a positive ROC curve (P=0.001), as there was for all child-reported wheezing (P=0.048). CONCLUSIONS: Airway hyperresponsiveness to methacholine in children relates closely with asthma and wheezing reported by either the parent or the child. In addition, the results confirm that respiratory symptoms and airway hyperresponsiveness are common in Canadian children, and that airway hyperresponsiveness may be found in children with no history of respiratory illness either at present or in the past.